The state of medical assistance to patients with diabetic retinopathy in Russian Federation: results of evaluation by TADDS WHO program - V. V. Neroev; L. A. Katargina; O. V. Zaitseva; T. D. Okhotsimskaya; R. A. Fedotov; V. A. Fadeeva; D. O. Arestov; Z. V. Kurchaeva (Российский офтальмологический журнал, 2018)
The paper analyzes the data of a survey, conducted among the chief ophthalmologists in 34 regions of Russian Federation, on the state of medical care of patients with diabetic retinopathy. The questionnaire of the survey was developed by WHO within the international program "Tool for the Assessment of Diabetic Retinopathy and Diabetes Management System" (TADDS) and adapted to Russia’s conditions. We analyzed the scope of practical use of regulatory documents, the availability of medical care, screening quality, diagnosis, monitoring and treatment of diabetic retinopathy, cooperation of medical facilities, and education of medical staff // Russian Ophthalmological Journal, 2016; 2: 5-10. doi: 10.21516/2072-0076-2016-9-2-5-10.